Pengaruh Pertumbuhan Penduduk, Tingkat Pengangguran Terbuka dan Tenaga Kerja Sektor Formal Terhadap Pertumbuhan Ekonomi Indonesia: Studi Panel 2020-2024 - Selvia Yunus Diu; Sri Endang Saleh; Boby Rantow Payu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the effect of population growth, open unemployment rate, and formal sector labor on Indonesia's economic growth using panel data from 34 provinces during 2020–2024. The study employs a quantitative approach with panel data regression using the Random Effect Model (REM). The results indicate that population growth has a positive and significant effect on economic growth. Meanwhile, open unemployment rate and formal sector labor have negative but statistically insignificant effects. Simultaneously, the independent variables are significant at the 10 percent level but not at the 5 percent level. These findings suggest that demographic dynamics and labor market conditions partially explain regional economic growth disparities in Indonesia. Keywords: Population Growth, Open Unemployment, Formal Labor, Economic Growth.